Relationships Education Level Completed Immunization Mother With Baby Basics At Age 12 Months In Puskesmas Kampar Kiri Hilir 2019: Relationships Education Level Completed Immunization Mother With Baby Basics At Age 12 Months In Puskesmas Kampar Kiri Hilir 2019 - Nelly Karlinah (Journal of Midwifery and Nursing, 2020)
The purpose of health development is to achieve a healthy ability for each resident in order to realize the optimal degree of public health (Budioro, 2001). In the sphere of health care, preventive field is a top priority in implementing the National Health System (NHS) immunization is one form of health intervention that is very effective in reducing the mortality rate of infants and toddlers (Ranuh, 2008). Achievement of Universal Child Immunization (UCI) is the achievement of a complete primary immunization in infants (0-11 months). UCI is a picture of the village or villages with ? 80% (Gavi, 2018). This research is an observational analytic study with case control study design, research that began with mengidentifikasikelompok with certain effects (cases) and without the effects of groups (control). The research sample some babies who have reached the age of 12 months from the population cases. The results showed the above table, it is known that out of 30 respondents in incomplete immunization status, 14 respondents (23.3%) had one child and who had> 1 child as much as 16 respondents (26.7%). Of the 30 respondents to the full immunization status, 8 respondents (13.33%) have one child and 22 respondents (36.7%) had> 1 child. The results of the analysis obtained from the chi square test showed that the p value 0.108 (> ? = 0.05), so that Ha is rejected,